2016
DOI: 10.1016/j.ymeth.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations in tissue engineering research: Case studies in translation

Abstract: Tissue engineering research is a complex process that requires investigators to focus on the relationship between their research and anticipated gains in both knowledge and treatment improvements. The ethical considerations arising from tissue engineering research are similarly complex when addressing the translational progression from bench to bedside, and investigators in the field of tissue engineering act as moral agents at each step of their research along the translational pathway, from early benchwork a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 56 publications
0
55
0
Order By: Relevance
“…[86][87][88] These involve questions related to the novelty of the technology itself, but also regarding its integration with biologic products (e.g. stem cell technology).…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[86][87][88] These involve questions related to the novelty of the technology itself, but also regarding its integration with biologic products (e.g. stem cell technology).…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…[87,88] Other factors worth to consider include data integrity and appropriate study design, which could prevent premature transition from the bench to the bedside stage. [86] This bedside stage, which involves clinical trials, predominantly addresses questions related to the participants; selection of participants, and most importantly, the risks for the participant, which should be appropriate compared with the potential benefits on the larger scale. Lastly, there are society-related ethical considerations, which include the public's perception of the biofabrication field.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…It is important to realize that, at any stage, the results of well-designed and properly conducted research might not lead forward, but back or in a different direction than expected. It is also important to refine and expand knowledge at an earlier stage of the research or to explore and develop newly identified possibilities [4].…”
Section: Res Med Eng Scimentioning
confidence: 99%
“…The choice of animal models and their humane and appropriate use helps to ensure that the research transition from animals to humans adheres to principle of "modest translational distance" described by Jonathan Kimmerlman. Translational distance (TD) refers to the number and size of inferential loops from animals to humans-in other words, it measures uncertainty [4]. In order to move from preclinical to first-in-human and other early stage trials, several questions must be answered in the affirmative [4]:…”
Section: Res Med Eng Scimentioning
confidence: 99%
See 1 more Smart Citation